The Clinical Significance and Mechanisms of REG4 in Human Cancers - Zhang, Junyan; Zhu, Zhi; Miao, Zhifeng; Huang, Xuanzhang; Sun, Zhe; Xu, Huimian; Wang, Zhenning (Frontiers in Oncology, 2021)
Regenerating islet-derived type 4 (REG4), a member of the calcium-dependent lectin gene superfamily, is abnormally expressed in various cancers, such as colorectal, gastric, gallbladder, pancreatic, ovarian, prostate, and lung cancer. REG4 is associated with a relatively unfavorable prognosis and clinicopathologic features in cancers, including advanced tumor and nodal stage, histological differentiation, and liver and peritoneal metastasis. Moreover, REG4-positive cancer cells show more frequent resistance to chemoradiotherapy, especially 5-FU-based chemotherapy. REG4 participates in many aspects of carcinogenesis, including cell proliferation, apoptosis, cell cycle, invasion, metastasis, and drug resistance. The underlying mechanisms are complex and involve a series of signaling mediators and multiple pathways. Thus, REG4 may be a potential diagnostic and prognostic biomarker as well as a candidate therapeutic target in cancer patients. In this review, we systematically summarize the advances about the clinical significance, biological functions, and mechanisms underlying REG4 in cancer to provide new directions for future cancer research.